ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Dede Pramurza (JISOS: JURNAL ILMU SOSIAL, 2023)
Fraud is an attempt to violate legal provisions, which is carried out deliberately with various specific purposes, such as to manipulate or create wrong financial reports to certain parties. The research analyzes the influence of variable pressure proxied by financial stability. Opportunity that proxied by ineffective monitoring. Rationalization that proxied by change of auditor. Capability that proxied by change of direksi. The population of this research is the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2017-2021. Samples of 3 companies were obtained by purposive sampling. With the results of research on financial stability, effective monitoring, rationalization data analysis method using rationalization, and capability does not affect financial statement fraud